Atmospheric Composition and Cloud Cover Observations - Voiculescu, Mirela (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This is a Special Issue of Atmosphere presenting recent results of experimental and theoretical investigations of atmospheric compositions and clouds, largely based on remote sensing.